Intestinal prolapse through the vagina. Issue 816 (October 1993) - Patankar, R. V.; Scott, S. D.; McGinn, F. P.
Abstract : We describe the case of a 68-year-old woman who presented with an acute onset spontaneous vaginal vault rupture and intestinal prolapse through the vagina. Results of a literature survey are presented and the causes of vaginal vault rupture are discussed.